HOMOTHETIC FUNCTIONS WITH ALLEN'S PERSPECTIVE AND ITS GEOMETRIC APPLICATIONS - Aydin, M. E.; Ergut, M. (Univ Kragujevac, Fac Science, 2014)
In this paper, we completely classify the homothetic functions of 2 variables by using their Allen's matrices. We give some applications of Allen's matrices to composite functions. Several geometric results are also obtained for graphs of homothetic functions.
Keywords: Homothetic production function; Allen's elasticity of substitution; Generalized Cobb-Douglas production function; Generalized ACMS production function